Pengaruh Electronic Word of Mouth, Customer Experience, dan Persepsi Harga terhadap Loyalitas Konsumen Fishing Masis Driyorejo Gresik - Helminatus Sholicha; Estik Hari Prastiwi (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the effect of Electronic Word of Mouth (E-WOM), customer experience, and price perception on consumer loyalty at Fishing MaSis Driyorejo, Gresik Regency. This research employs a quantitative approach using a survey method. Data were collected from 100 respondents who were customers of Fishing MaSis Driyorejo through the distribution of questionnaires using a five-point Likert scale. The sampling technique applied was purposive sampling, while data analysis was conducted using multiple linear regression with the assistance of SPSS version 25. The results indicate that, partially, customer experience and price perception have a positive and significant effect on consumer loyalty, whereas Electronic Word of Mouth does not have a significant effect. However, simultaneously, E-WOM, customer experience, and price perception have a significant effect on consumer loyalty. The coefficient of determination shows that these three independent variables explain 74.8% of the variation in consumer loyalty, while the remaining percentage is influenced by other factors outside the scope of this study. These findings emphasize that customer experience and price perception are dominant factors in shaping consumer loyalty in fishing tourism destinations and should therefore be the main focus of management and marketing strategies.